Identification of High-Risk Pregnancies in a Remote Setting Using Ambulatory Blood Pressure: The MINDI Cohort - González-Fernández, Doris; Pons, Emérita del Carmen; Rueda, Delfina; Sinisterra, Odalis Teresa; Murillo, Enrique; Scott, Marilyn E.; Koski, Kristine G. (Frontiers in Public Health, 2020)
Background: Ambulatory blood pressure is a potential tool for early detection of complications during pregnancy, but its utility in impoverished settings has not been assessed. This cross-sectional study aimed to determine whether maternal infections, nutrient deficiencies and inflammation (MINDI) were associated with four measures of maternal blood pressure (BP) and to determine their association with symphysis-fundal-height (SFH). Methods: Environmental and dietary factors, intake of iron and a multiple-nutrient supplement (MNS), markers of inflammation, protein, anemia, folate, vitamins B12, A and D status, and urogenital, skin, oral and intestinal nematode infections were measured in indigenous pregnant Panamanian women. Stepwise multiple linear and logistic regression models explored determinants of systolic and diastolic blood pressure (SBP, DBP), hypotension (SBP<100 and DBP<60), mean arterial pressure (MAP), elevated MAP (eMAP), and pulse pressure (PP). Associations of BP with intestinal nematodes and with SFH Z scores (≥16 wk) were also explored. Results: Despite absence of high SBP or DBP, 11.2% of women had eMAP. Furthermore, 24.1% had hypotension. Linear regression showed that hookworm infection was associated with higher SBP (P=0.049), DBP (P=0.046) and MAP (0.016), whereas Ascaris was associated with lower DBP (P= 0.018) and MAP (0.028). Trichomonas was also associated with lower SBP (P<0.0001) and MAP (P=0.009). The presence of Trichuris (OR: 6.7, 95% CI 1.0-44.5) and folic acid deficiency (OR: 6.9, 95% CI 1.4-33.8) were associated with increased odds of eMAP. The odds of low BP was higher in the presence of Ascaris (OR: 3.63 ± 2.28, P= 0.040), but odds were lowered by MNS (OR: 0.35 ± 0.11, P= 0.001), more intake of animal-source foods/wk (OR: 0.7, 95% CI 0.5-0.9) and by higher concentrations of IL17 (OR: 0.87 ± 0.05, P= 0.016). Conclusion: MINDI were bi-directionally associated with blood pressure indicators. In this MINDI cohort, infections, nutrients and cytokines both raised and lowered BP indices. The presence of eMAP identified pregnant women at risk of hypertension whereas low PP was associated with lower SFH. Therefore, MAP and PP may help in detecting women at risk of adverse pregnancy outcomes in settings with limited access to technology.